Proses Pembuktian Pada Tahap Penyidikan Tindak Pidana Ancaman Kekerasan Melalui Telepon (Study Kasus Di Polres Klungkung) - I Putu Arya Wiguna Artana; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Jurnal Analogi Hukum, 2021)
In the era of globalization, many things that make human behavior and habits become changed from lifestyle to advanced thinking, the progress of the nation today becomes a positive thing but in the implementation the day-day, many people are still affected by technology based on information technology. The influence of social media in this community makes many lifestyle changes that are positive and negative. On the positive side, people quickly know the development in their country of residence, and from the negative side, many people think that it is lawful all means to achieve their life goals such as committing acts that harm many parties ranging from fraud to criminal acts. Each person can choose what will be done and the consequences obtained from the deeds done. The occurrence of unlawful acts certainly gets a commensurate reward but with a due process that is through various resistance such as investigation and proof. Which affects the evidentiary process in the level of investigation of perpetrators of violent threats through telephone media is the difficulty of giving directions to the victim to provide honest information, covering up the reason for the perpetrator to make threats, from the information before the investigators and the victim often cover up the problem that actually comes from the victim himself.